Anteseden dari Brand Loyalty pada Brand Smartphone di Indonesia - Novita Romadhowati (Peneliti.net, 2023)
The study looked at the relationships between perceived quality, brand trust, and knowledge, as well as between perceived quality, brand trust, knowledge, customer satisfaction, also brand loyalty. This study,